HAPPINESS, EXISTENCIAL THOUGHT AND ACADEMIC PERFORMANCE IN UNIVERSITY STUDENTS OF LIMA - ESPÍRITU SALINAS, Natividad (2021)
Investigated happiness, existential thought and academic performance measured with the historical average of notes of 264 male and female students from different careers of a private university in Lima. Happiness Scale of Alarcón (2006) and Test of Existential Thought of Espíritu, Canales, Luna y Torres (2018) were applied.Calculating Spearman’s Rho it was found a high positive correlation between happiness and significant existential thought p <0.01, between happiness and the essence of existential thought, as well the spiritual, between happiness and academic performance p <0.05. They correlate in a significant negative the pragmatic of the existential thought with the academic performance p <0.01. In existential thought,  items “I see life as a gift”, “I have a motive, a reason to live” and “I accept myself as I am” are correlated significantly higher with happiness. No correlation was found between happiness and pragmatic in existential thought (r= -0.005, p = 0.929), nor between existential thought and academic performance (r = -0.113), p = 0.067). The results are applicable for university tutoring purposes.